CpG Single-Site Methylation Regulates TLR2 Expression in Proinflammatory PBMCs From Apical Periodontitis Individuals - Bordagaray, María José; Fernández, Alejandra; Astorga, Jessica; Garrido, Mauricio; Hernández, Patricia; Chaparro, Alejandra; Lira, María Jesús; Gebicke-Haerter, Peter; Hernández, Marcela (Frontiers in Immunology, 2022)
Introduction Apical periodontitis (AP) is a common oral disease caused by the inflammatory destruction of the periapical tissues due to the infection of the root canal system of the tooth. It also contributes to systemic bacterial translocation, where peripheric mononuclear blood cells (PBMCs) can act as carriers. Toll-like receptor (TLR) 2 mediates the response to infection and activates inflammatory responses. DNA methylation can be induced by bacteria and contributes to the modulation of this response. Despite the evidence that supports the participation of PBMCs in immune-inflammatory disorders, the inflammatory profile and epigenetic regulatory mechanisms of PBMCs in AP individuals are unknown. Aim To determine TLR2 gene methylation and inflammatory profiles of PBMCs in AP. Methods Cross-sectional exploratory study. Otherwise, healthy individuals with AP (n=27) and controls (n=30) were included. PMBCs were isolated by a Ficoll gradient, cultured for 24 hours, and both RNA and DNA were extracted. DNA was bisulfite-treated, and specific sites at the promoter region of the TLR2 gene were amplified by qPCR using validated primers. To verify its amplification, agarose gels were performed. Then, the PCR product was sequenced. mRNA expression of TLR2 was determined by qPCR. The soluble levels of 105 inflammatory mediators were first explored with Proteome Profiler Human Cytokine Array Kit. Consequently, tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-10, IL-6Rα, IL-1β, and IL-12p70 levels were measured by Multiplex assay. Results PBMCs from individuals with AP demonstrated a proinflammatory profile showing higher soluble levels of TNF-α, IL-6, and IL-1β compared to controls (p<0.05). Higher TLR2 expression and higher global methylation pattern of the promoter region of the gene were found in AP compared to controls (p<0.05). The CpGs single-sites at positions -166 and -146 were completely methylated, while the site -102 was totally unmethylated, independently of the presence of AP. DNA methylation of CpG single-sites in positions -77 and +24 was positively associated with TLR2 expression. Conclusions PBMCs from AP subjects show a hyperinflammatory phenotype and TLR2 upregulation in association with single CpG-sites’ methylation from the TLR2 gene promoter, thereby contributing to a sustained systemic inflammatory load in individuals with periapical endodontic diseases.